Synthesis of Recommendations From 25 Countries and 31 Oncology Societies: How to Navigate Through Covid-19 Labyrinth - Kamposioras, Konstantinos; Mauri, Davide; Papadimitriou, Konstantinos; Anthoney, Alan; Hindi, Nadia; Petricevic, Branka; Dambrosio, Mario; Valachis, Antonis; Kountourakis, Pantelis; Kopecky, Jindrich; Kuhar, Cvetka Grašič; Popovic, Lazar; et al. (Frontiers in Oncology, 2020)
Introduction: Pandemic COVID-19 is an unexpected challenge for the oncological community, indicating potential detrimental effects on cancer patients. Our aim was to summarize the converging key points providing a general guidance in order to support decision making, pertaining to the oncologic care in the middle of a global outbreak. Methods: We did an international online search in twenty five countries that have managed a surge in cancer patient numbers. We collected the recommendations from thirty one medical oncology societies. Results: By synthesizing guidelines for a) oncology service delivery adjustments, b) general and specific treatment adaptations and c) discrepancies from guidelines comparison, we present a clinical synopsis with the forty more crucial statements. A Covid-19 risk stratification base was also created in order to obtain a quick, objective patient assessment and a risk-benefit evaluation on a case-by-case basis. Conclusions: In an attempt to face these complex needs and due to limited understanding of COVID-19, a variability of recommendations based on general epidemiological and infectious disease principles rather than definite cancer-related evidence has evolved. Additionally, the absence of an effective treatment or vaccine requires the development of cancer management guidance, capitalizing on comprehensive COVID-19 oncology experience globally.